Naturressursene og verdenspolitikken på Svalbard 1596-2011 - Berg, Roald (Nordlit, 2012)
The history of Spitsbergen/Svalbard has been characterized by a combination of masculine heroism and continuous struggle for the natural resources at the islands. In the beginning, from the 16th century, it was an international struggle for the harvesting of the whale and walrus; its value was so great that international conflicts led to the development of such doctrines as mare clausum and mare liberum ininternational law. The competition for the utilization of the coal resources led the Americans near annexation during the first decade of the 20th century before Norway received sovereignty over the islands after the first world war and the services of the Norwegian merchant fleet during that war. After the cold war the oil deposits in the Barents Sea might trigger another period of resource struggle at the islands and the oceans around them.